2006
DOI: 10.17744/mehc.28.2.ef384lm8ykfujum5
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Reenactment: Rethinking Borderline Personality Disorder When Diagnosing Sexual Abuse Survivors

Abstract: Adult survivors of sexual trauma often experience symptoms related to their childhood experiences that are analogous to many of the diagnostic criteria of Borderline Personality Disorder (BPD). This article examines these symptoms in the context of a trauma framework and postulates that mental health counselors need to consider if the symptomatic behaviors are more indicative of a post-traumatic response, specifically trauma reenactment. Recognizing self-harming behaviors in adult survivors as reenactments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Despite the mind blocking knowledge of the abuse from conscious awareness, the traumatic experience takes a toll. Often, these effects manifest indirectly through physical and psychological symptoms that occur without apparent cause (Beck, Elzevier, Pelger, Putter, & Voorham-van der Zalm, 2009;Ross, 2005;Courtois, 1997;Briere & Spinazzola, 2005;Kaehler & Freyd, 2009;Trippany, Helm, & Simpson, 2006). Because the individual cannot consciously connect the sequelae of betrayal traumas with a cause, betrayal has the potential to induce more complex and prolonged distress.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the mind blocking knowledge of the abuse from conscious awareness, the traumatic experience takes a toll. Often, these effects manifest indirectly through physical and psychological symptoms that occur without apparent cause (Beck, Elzevier, Pelger, Putter, & Voorham-van der Zalm, 2009;Ross, 2005;Courtois, 1997;Briere & Spinazzola, 2005;Kaehler & Freyd, 2009;Trippany, Helm, & Simpson, 2006). Because the individual cannot consciously connect the sequelae of betrayal traumas with a cause, betrayal has the potential to induce more complex and prolonged distress.…”
Section: Introductionmentioning
confidence: 99%
“…Higher incidences of physical complaints such as irritable bowel syndrome, chronic pelvic pain, and musculoskeletal pain have been documented in individuals with a history of interpersonal abuse (Beck, Elzevier, Pelger, Putter, & Voorham-van der Zalm, 2009;Ross, 2005), including those maintaining little or no memory of documented abuse (Courtois, 1997). The effects of this abuse are seen psychologically as dissociation, anxiety, depression (Briere & Spinazzola, 2005), and interpersonal difficulties that are sometimes extreme enough to fit a diagnosis of borderline personality disorder (Kaehler & Freyd, 2009;Trippany, Helm, & Simpson, 2006). Even if memory of abuse is largely intact, these memories are often of a disjointed and "unshareable" nature, which leads to difficulty seeking satisfying psychological help (van der Kolk & Fisler, 1995).…”
mentioning
confidence: 99%
“…A chart-review study found a prevalence of past sexual abuse of 50% among inpatient adolescents with BPD (Westen, Ludolph, Misle, Ruffins, & Block, 1990). Given these findings, some have speculated that BPD represents complex PTSD, suggesting that past trauma drives the ED characteristic of BPD (Cloitre, Garvert, Weiss, Carlson, & Bryant, 2014; Ford & Courtois, 2014; Trippany, Helm, & Simpson, 2006; van der Kolk, Pelcovitz, Roth, & Mandel, 1996). Other researchers have suggested that past abuse or trauma are neither necessary nor sufficient for a BPD diagnosis (Zanarini et al, 1997).…”
Section: The Development Of Ed In Bpdmentioning
confidence: 99%